Distance learning system of the professional military education institution: problematic issues of formation - Tyshchenko , Maksym; Shapran , Olexander; Sudnikov , Yevgen; Makhno , Yevgenii; Gawliczek, Piotr Jerzy (Civitas et Lex, 2023)
Modern trends in the education development require directing efforts to the development of distance learning in the Ukrainian Armed Forces as one of the effective tools for implementing the model of continuous training. The article is devoted to highlighting the problematic issues of formation the distance learning system of the professional military education institution. There are analyzed the main subsystems of the distance learning system of the professional military education institution, which determine the architecture of the system and its intended purpose. The analysis of the distance learning systems formation made it possible to determine the central objectives of certain types of the distance learning system providing and factors that negatively affect the distance learning system formation. An overview of the problematic issues of the distance learning system formation regarding a professional military education institution shows that it is necessary to approach the formation of a distance learning system differently, taking into account the existing limitations.